2008
DOI: 10.1161/circulationaha.108.796136
|View full text |Cite
|
Sign up to set email alerts
|

Downloadable Algorithm to Reduce Inappropriate Shocks Caused by Fractures of Implantable Cardioverter-Defibrillator Leads

Abstract: Background-The primary method for monitoring implantable cardioverter-defibrillator lead integrity is periodic measurement of impedance. Sprint Fidelis leads are prone to pace-sense lead fractures, which commonly present as inappropriate shocks caused by oversensing. Methods and Results-We developed and tested an algorithm to enhance early identification of lead fractures and to reduce inappropriate shocks. This lead-integrity algorithm, which can be downloaded into presently implanted implantable cardioverter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
131
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 16 publications
2
131
0
1
Order By: Relevance
“…Excluding recalled leads, ventricular oversensing accounts for less than 10% of inappropriate shocks, but it often results in repetitive shocks and severe symptoms [82,[142][143][144]. Recently introduced features reduce inappropriate therapies from oversensing of physiologic T waves and nonphysiologic signals related to pace-sense lead failures as discussed below.…”
Section: Ventricular Oversensingmentioning
confidence: 99%
See 3 more Smart Citations
“…Excluding recalled leads, ventricular oversensing accounts for less than 10% of inappropriate shocks, but it often results in repetitive shocks and severe symptoms [82,[142][143][144]. Recently introduced features reduce inappropriate therapies from oversensing of physiologic T waves and nonphysiologic signals related to pace-sense lead failures as discussed below.…”
Section: Ventricular Oversensingmentioning
confidence: 99%
“…The present algorithms were developed to identify impending lead failures on recalled leads, notably the Sprint Fidelis. These algorithms might not be appropriate for detecting failures in other leads [144]. There is a high false-positive rate when using these algorithms, and caregivers must carefully review the device data that caused the alert to ensure the lead experienced a true failure [145].…”
Section: Lead-related Oversensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient-alert features have been implemented in ICDs for detection of system-related complications, for example acoustic alerts. Swerdlow et al [9] demonstrated that the Medtronic lead integrity alert algorithm triggered an acoustic alert of impending inappropriate shocks at least 3 days in advance in 76% of patients with lead failure. However, although these acoustic alerts are a useful tool facilitating early detection of system-related complications, they are insensitive and prone to falsepositive evaluations [10,11].…”
Section: Monitoring Of System Integritymentioning
confidence: 99%